Assessing the Digital Literacy of Children in Upper Primary Education - Atkins, Lucy (2012)
As technology becomes more pervasive in our daily lives, concern is growing about the effects this may have on the youngest generations. Some believe that technological advancements have positively changed the way learners think, leading to a generation who are more adept with technology. But there are doubts about this argument, since many children struggle with information retrieval and evaluation. For these reasons, interest in educating learners about successful ICT use is increasing. This research therefore examines the area of digital literacy, focusing specifically on the skills existing in key stage 2 children. The choice of this age group was influenced by the observation that there is a lack of empirical research in this area, despite the knowledge that children are engaging with technology from an ever younger age. The research approach adopted consists of a researcher-produced test of digital literacy skills, complemented by small group interviews. The findings from this research show that children are not as digitally literate as we are often lead to believe and that their experiences with ICT are far from extraordinary. However, it would appear that the skills associated with digital literacy develop gradually as the child progresses through primary schooling. The main conclusions drawn from this study are that greater links need to be made between home and school ICT use. This dissertation closes with some suggestions for possible further avenues of research in the area that were prompted by the current findings.